Compliance of Oral Snuff (Naswar) Packaging and Sales Practices with National Tobacco Control Laws and the Relevant Articles of Framework Convention on Tobacco Control in Khyber Pakhtunkhwa Pakistan. Issue 12 (17th August 2020) - Ahmad, Fayaz; Khan, Zohaib; Siddiqi, Kamran; Khan, Muhammad Naseem; Boeckman, Melanie; Dregger, Steffen; Bauld, Linda; Zeeb, Hajo; Forberger, Sarah
Abstract: Introduction: Smokeless tobacco (SLT) is a significant contributor to tobacco-related harm in Pakistan but its control has lags behind that of combustible tobacco. We assessed the compliance of Naswar's (a widely used SLT product in the Southeast Asia) packaging and sales practices with the national legislations and relevant articles of the WHO framework convention on tobacco control (FCTC). Aims and Methods: A cross-sectional observational audit was conducted in three districts of Pakistan. We recruited 286 general point of sale (GPOS) and exclusive Naswar sellers (ENS) through a multistage cluster sampling strategy. Data were gathered on packaging and labeling practices of Naswar and advertisement and promotion practices inside and outside the shops. Statistical tests for association between the dependent variable-advertisement practices, and independent variables-area and vendor types were conducted. Results: We analyzed 133 and 49 unique Naswar products sold in 229 GPOS and by 57 ENS, respectively. None of the local products had any written or pictorial health warning. More than half of retailers used one or two methods of advertising Naswar inside the shops while only 9% advertised outside the shops. ENS were more likely to be noncompliant with tobacco advertisement and promotion compared with GPOS. Conclusions: The study presents first insights on the compliance of Naswar packaging and sale practices with local regulations and WHO FCTC provisions in Pakistan. Almost all products were on display in the shops and none of the local products had any health warning or contents disclosure on the packages. Implications: Naswar is a form of SLT used extensively in Pakistan, Central Asia, and Pashtun populations across the globe. This study provides an important insight into the Naswar retail environment in a geographical setting where the use of Naswar is endemic. The study brings to fore previously unreported issues like an urban–rural disparity, and differences between exclusive and nonENS, with regards to Naswar advertisement and promotion. These findings have potential implication on the implementation of tobacco control retail policies. The lack of health warnings and free display of Naswar brands call for alignment of tobacco control efforts with the FCTC.